Öl und Souveränität. Petroknowledge und Energiepolitik in den USA und Westeuropa in den 1970er Jahren - Graf, Rüdiger (Quellen und Darstellungen zur Zeitgeschichte, 2014)
The importance of oil for modern economic and political regimes increased during the economic boom of the post-war decades. Yet in 1973-1974, rising oil prices and reduced production raised the specter of an uncertain future. Rüdiger Graf examines the national and international strategies formulated to deal with this challenge to political sovereignty, exploring the first oil crisis in the context of the transformational processes of the 1970s.